2011
DOI: 10.1208/s12249-011-9679-x
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancing and Sustaining AMG 009 Dissolution from a Matrix Tablet Via Microenvironmental pH Modulation and Supersaturation

Abstract: Abstract. The objective of this study was to investigate the combined effect of pH modifiers and nucleation inhibitors on enhancing and sustaining the dissolution of AMG 009 tablet via supersaturation. Several bases and polymers were added as pH modifiers and nucleation inhibitors, respectively, to evaluate their impact on the dissolution of AMG 009 tablets. The results indicate that sodium carbonate, among the bases investigated, enhanced AMG 009 dissolution the most. HPMC E5 LV, among the nucleation inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, due to super-saturation, the salt may sometimes precipitate out as the insoluble free form upon dissolution, forming a layer on the surface of the dissolving salt, which may result in low bioavailability of the drug. The addition of functional excipients, such as surfactants and pH modifiers, in the dosage forms have been reported to be an effective tool in improving the dissolution behavior of compounds with pH dependent solubility ( 5 , 6 ). Further, in vitro dissolution studies have shown that incorporating 15% sodium bicarbonate (NaHCO 3 ) as an alkalizing agent in the solid dosage form of GDC-0810 can enhance its release via micro-environmental pH modulation, resulting in increased dissolution ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to super-saturation, the salt may sometimes precipitate out as the insoluble free form upon dissolution, forming a layer on the surface of the dissolving salt, which may result in low bioavailability of the drug. The addition of functional excipients, such as surfactants and pH modifiers, in the dosage forms have been reported to be an effective tool in improving the dissolution behavior of compounds with pH dependent solubility ( 5 , 6 ). Further, in vitro dissolution studies have shown that incorporating 15% sodium bicarbonate (NaHCO 3 ) as an alkalizing agent in the solid dosage form of GDC-0810 can enhance its release via micro-environmental pH modulation, resulting in increased dissolution ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies (20), it was found that, when Na 2 CO 3 was removed from the formulation and dissolved in the dissolution medium prior to tablet dissolution study, only 4% AMG 009 was released from the matrix tablets. This indicates that the dissolution enhancement in aforementioned study is a result of microenvironmental pH modulation by Na 2 CO 3 because the pH of bulk dissolution medium is the same before and after dissolution and is not impacted by such a small amount of Na 2 CO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…These facts indicate that a strong basic pH modifier, such as sodium carbonate with a pk a value of 10.3, is needed in the dosage form to increase the pH of the microenvironment and thus the solubility, resulting in increased dissolution of AMG 009. The detailed study and selection of basic pH modifiers were described in a previous publication (20). Figure 3 shows the dissolution profiles of matrix and bilayer capsules.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, weak organic acids, such as ascorbic, adipic, citric, fumaric, glutaric, succinic, malic, tartaric acids, are used to decrease microenvironmental pH of weakly basic drugs. Various weak bases, such as sodium carbonate, sodium bicarbonate, magnesium oxide, calcium carbonate, potassium phosphate, sodium phosphate, and so forth, are used to increase the microenvironmental pH and thereby enhance the dissolution rate of poorly water-soluble weakly acidic drugs (Bi et al 2011b;Tran et al 2009. The pH modifiers may also prevent or retard conversion of salts into their unionized forms and, therefore, the dissolution rates remain high (Badawy et al 2006).…”
Section: Modulation Of Microenvironmental Ph By Using Ph Modifiersmentioning
confidence: 99%
“…For a weakly acidic drug, AMG009 with poor intrinsic solubility (0.6 μg/mL), Bi et al (2011aBi et al ( , 2011b prepared solid dispersions by using various nucleation inhibitors, such as HPMCE5 LV, HPMC K100 LV, plasdone K-17 (PVP K17); pHmodifiers, such as sodium carbonate, sodium bicarbonate, tromethamine, sodium acetate, sodium phosphate; and sodium citrate dihydrate. Both the nucleation inhibitor and the pH modifier were necessary to increase the dissolution rate and maintain supersaturation of the drug in the dissolution media.…”
Section: Use Of Ph Modifiers In Solid Dispersionmentioning
confidence: 99%